Drugs with anticholinergic effects and cognitive impairment, falls and all‐cause mortality in older adults: A systematic review and meta‐analysis. (20th May 2015) - Ruxton, Kimberley; Woodman, Richard J.; Mangoni, Arduino A.
<x xml:space="preserve">Abstract</x> Aim The aim was to investigate associations between drugs with anticholinergic effects (DACEs) and cognitive impairment, falls and all‐cause mortality in older adults. Methods A literature search using CINAHL, Cochrane Library, Embase and PubMed databases was conducted for randomized controlled trials, prospective and retrospective cohort and case‐control studies examining the use of DACEs in subjects ≥65 years with outcomes on falls, cognitive impairment and all‐cause mortality. Retrieved articles were published on or before June 2013. Anticholinergic exposure was investigated using drug class, DACE scoring systems (anticholinergic cognitive burden scale, ACB; anticholinergic drug scale, ADS; anticholinergic risk scale, ARS; anticholinergic component of the drug burden index, DBIAC) or assessment of individual DACEs. Meta‐analyses were performed to pool the results from individual studies. Results Eighteen studies fulfilled the inclusion criteria (total 124 286 participants). Exposure to DACEs as a class was associated with increased odds of cognitive impairment (OR 1.45, 95% CI 1.16, 1.73). Olanzapine and trazodone were associated with increased odds and risk of falls (OR 2.16, 95% CI 1.05, 4.44; RR 1.79, 95% CI 1.60, 1.97, respectively), but amitriptyline, paroxetine and risperidone were not (RR 1.73, 95% CI 0.81, 2.65; RR 1.80, 95% CI 0.81, 2.79; RR 1.39, 95% CI 0.59, 3.26, respectively). A unit increase in the ACB scale was associated with a doubling in odds of all‐cause mortality (OR 2.06, 95% CI 1.82, 2.33) but there were no associations with the DBIAC (OR 0.88, 95% CI 0.55, 1.42) or the ARS (OR 3.56, 95% CI 0.29, 43.27). Conclusions Certain individual DACEs or increased overall DACE exposure may increase the risks of cognitive impairment, falls and all‐cause mortality in older adults.